2016
DOI: 10.5694/mja15.00955
|View full text |Cite
|
Sign up to set email alerts
|

First reported outbreak of locally acquired hepatitis E virus infection in Australia

Abstract: This is the first reported HEV outbreak in Australia. HEV should be considered in patients presenting with a compatible illness, even without a history of overseas travel. Pork products should be thoroughly cooked before consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 21 publications
0
44
0
Order By: Relevance
“…On the other hand, previous animal models and cell culture studies confirmed the presence of infectious HEV in contaminated commercial pork liver and demonstrated HEV resistance to some of the conventional heat treatments used in the food industry (Barnaud et al 2012; Berto et al 2013; Feagins et al 2008). This is especially important with regards to the products investigated in this study, as it has recently been reported that consuming contaminated pork pâtés and sausages led to an outbreak in Australia (Yapa et al 2016). It is also of great concern that HEV isolates identified in this and previous studies conducted in Canada, show high homology to clinical isolates detected in this country (Wilhelm et al 2015a) (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, previous animal models and cell culture studies confirmed the presence of infectious HEV in contaminated commercial pork liver and demonstrated HEV resistance to some of the conventional heat treatments used in the food industry (Barnaud et al 2012; Berto et al 2013; Feagins et al 2008). This is especially important with regards to the products investigated in this study, as it has recently been reported that consuming contaminated pork pâtés and sausages led to an outbreak in Australia (Yapa et al 2016). It is also of great concern that HEV isolates identified in this and previous studies conducted in Canada, show high homology to clinical isolates detected in this country (Wilhelm et al 2015a) (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…While in developing countries HEV causes large epidemics, sporadic cases of locally acquired HEV infections are increasingly reported in developed countries (Teshale et al 2010). Although the epidemiological significance of HEV infections in industrialized countries requires further study, the zoonotic transmission of HEV via the consumption of raw or undercooked pork, wild boar, and deer meat has been confirmed by several studies (Bouamra et al 2014; Colson et al 2010; Masuda et al 2005; Renou et al 2014; Yapa et al 2016). HEV typically causes self-limiting, acute hepatitis with a low mortality rate of 1–4%, except for pregnant woman in endemic regions where the mortality rate can be up to 20% (Purcell and Emerson 2008).…”
Section: Introductionmentioning
confidence: 95%
“…In these studies, identical or near identical HEV sequences were detected in patients suffering from hepatitis E and animal products they had consumed: grilled wild boar meat in Japan [124], pig meat in Spain [125] and ficatellu sausage from Corsica [126]. Several reports in Japan, France, Spain and Australia have also linked sporadic cases or outbreaks of hepatitis E with the consumption of raw or undercooked pork or wild boar products (meat, liver, liver paté, ficatellu or liver-based stuffing) without direct proof that these food items were the source of the infection [126,127,128,129,130,131,132,133]. These data are supported by studies showing that the consumption of pork and wild-boar meat and processed products is a risk factor for autochthonous HEV infection and HEV seropositivity [129,134,135,136,137,138].…”
Section: Transmission Pathways Of Zoonotic Hevmentioning
confidence: 99%
“…HEV-3 and HEV-4 RNA is present throughout the pork food chain worldwide [130,133,139,140,141,142,143]. Studies have reported that 3%–11% of pig liver samples at the slaughterhouse are HEV positive in France (4%) [144], the Netherlands (6.5%) [145], Czech Republic (5%) [141], Italy (6%) [140], Spain (3%) [140], the United Kingdom (3%) [146], Japan (5%) [147] and the US (11%) [148].…”
Section: Transmission Pathways Of Zoonotic Hevmentioning
confidence: 99%
“…Furthermore, these studies focused on patients displaying clinical symptoms, representing a minority of individuals infected with HEV gt3. Two local HEV outbreaks were studied in which asymptomatically infected persons were traced; consumption of pork liver pâté and shellfish were the most likely source of infection in a restaurant in Australia and on a cruise ship, respectively [13,14]. …”
Section: Introductionmentioning
confidence: 99%